Pengabdian Masyarakat Melalui Kuliah Kerja Nyata (KKN) Di Desa Salenrang Kabupaten Maros - Farsya Bani Asmara; Muhammad Iqbal; Feerzet Achmad; * Harmiansyah; Kiki Yulia Handayani (CV. SINAR HOWUHOWU, 2026)
Community Service Program (KKN) is a manifestation of the Tri Dharma of Higher Education, encouraging students to directly participate in community empowerment through education, research, and community service activities. This article reviews the implementation of the 13th National Community Service Program (KKN Kebangsaan) in 2025 in Salenrang Village, Bontoa District, Maros Regency, with a primary focus on tourism development. The work program included the development of a disaster mitigation map, the digitization of the Rammang Rammang tourist map, and the production of destination profile videos. Using a participatory approach, this program successfully encouraged community involvement in maintaining and managing local tourism potential. Results indicate increased community awareness regarding disaster mitigation and the use of technology in tourism promotion. This article also identifies several challenges, such as limited infrastructure and post-KKN program sustainability, and provides recommendations for developing future community service programs that are more sustainable and based on local potential.